Surveillance of the banks of reservoirs on the Drava River in Slovenia after extensive floods - Žvanut Pavel (E3S Web of Conferences, 2022)
The Slovenian section of the Drava River is 133 km long, and over this distance it has a descent of 148 m. Eight HPPs are located on this section (six directly in the river course, whereas the other two in derivation channels of the river). Ten concrete gravity dams, with a structural height between 17 and 54 m, created eight reservoirs. In addition to their main use for electricity generation, reservoirs are also used for floods mitigation, irrigation, industrial water use and recreation. At the beginning of November 2012, extremely high flows of the Drava River, which exceeded 100-year flood, caused floods in the middle and lower reaches of the river. Extraordinary visual geotechnical inspections of the banks, in order to determine any instability of them, were carried out immediately after this event. Numerous landslides and landslips were identified, as well as damage to nearby buildings, but also damage and threat to transport infrastructure. Damaged banks of reservoirs and damaged infrastructure were instantly rehabilitated. In the future, it is necessary to perform regular and extraordinary surveillance of the banks of reservoirs, drawing attention to damage that needs immediate rehabilitation, thus preventing the occurrence of eventual disastrous consequences.